Effects of earlens lens placement on sound field thresholds, tympanometric measurements and wideband acoustic immittance. (3rd January 2023) - Lucas, Matthew; Folkeard, Paula; Levy, Suzanne; Dundas, Drew; Scollie, Susan; Agrawal, Sumit
Abstract: Objective: The Earlens is a direct-drive hearing device consisting of a lens which physically displaces the umbo to achieve appropriate gain. The objective is to determine the clinical acceptability of clinical immittance measurements in Earlens wearers. Design: Controlled before-after within-subjects repeated measures study. Study sample: Data is reported for measurements obtained on 15 subjects (average age of 72.2 years) with data from 30 ears. Results: There was a small effect of lens placement on sound field thresholds in most subjects. The largest damping effect of 4 dB was observed at 1000 Hz. An average reduction of 0.17 mL was identified in compliance following lens placement ( p  < 0.05). An effect of the lens on power absorbance obtained at ambient and peak pressure was found. The lens resulted in an increase in power absorbance at low frequencies (below 500 Hz) and a decrease in the mid to high-frequency range of approximately 500–3500 Hz ( p  < 0.05). Conclusions: Lens wear had a small effect on audiometric thresholds and tympanometry for most patients. Clinicians who use compliance and power absorbance should take into consideration lens effects on these measurements. Additional work is required to develop clinical normative ranges of these measures for wearers of the Earlens.